Increasing students' performance by the method of regulated breath control - Venediktov, I.N.; Yarchikovskaya, L.V.; Mironova, O.V.; Leontyuk, A.M.; Sharonova, A.V.; Lukina, S.M. (Theory and Practice of Physical Culture, 2023)
Objective of the study was experimental confirmation of the effectiveness of using the method of regulated breathing control to improve the performance of students. Methods and structure of the study. The experiment involved 40 students of St. Petersburg State University aged 18-20, mastering "Elective disciplines in physical culture and sports." The students were divided into control (CG) and experimental (EG) groups of 20 people each. To determine the effectiveness of using the experimental method (regulated breathing control) in physical education classes, the following research methods were chosen: mental performance and stress resistance test (TMPSR), sustainable performance test (TST), VO2max test, 12-minute Cooper test. Results and conclusions. It has been experimentally proven that the regulated control of breathing allows you to use not only the muscles of the chest, shoulders, but also the muscles of the abdomen, as well as the diaphragm, which helps to restore the breathing technique and increase the performance of the bronchopulmonary apparatus.